Biological Control of Hemlock Woolly Adelgid: Implications of Adult Emergence Patterns of Two Leucopis spp. (Diptera: Chamaemyiidae) and Laricobius nigrinus (Coleoptera: Derodontidae) Larval Drop. Issue 4 (4th May 2021) - Dietschler, Nicholas J; Bittner, Tonya D; Trotter, R Talbot; Fahey, Timothy J; Whitmore, Mark C
Abstract: The hemlock woolly adelgid (Hemiptera: Adelgidae Adelges tsugae Annand) poses a serious threat to hemlocks in eastern North America, and ongoing research is focused on the identification and development of biological controls to protect and manage hemlock resources. Three predators native to the Pacific Northwest of North America that have been the focus of much research are Leucopis argenticollis (Zetterstedt), Leucopis piniperda (Malloch) (Diptera: Chamaemyiidae), and Laricobius nigrinus (Fender) (Coleoptera: Derodontidae). This study addresses the knowledge gap of adult Leucopis spp. emergence patterns, with comparisons to the timing of larval La. nigrinus drop for pupation. Adult Leucopis spp. emergence was observed in the lab from field-collected, adelgid-infested foliage from Washington state in 2019 and 2020. Adult Leucopis spp. were collected daily as they emerged from foliage collections and identified to species using morphological features; a subset was validated using DNA barcoding. Accumulated heating degree days were calculated to compare a standardized emergence timing across collections made at different locations and temperature regimes. The abundance of the two Leucopis spp. and of the combined Leucopis spp. and La. nigrinus varied among sites and years, and no species was consistently more abundant than the other. Evaluations of seasonal emergence trends of the three species determine the predator complex behaves in a temporally stratified and predictable way. Emergence of adult Le. argenticollis was observed first, followed by La. nigrinus larval drop, with Le. piniperda emerging at the end of larval drop, and finally a second emergence of Le. argenticollis .